Impactos da aquisição da linguagem tardia em alunos surdos em uma escola pública de Manaus - Lira, Thaynan Ionara Cordeiro (Brasil, 2022)
This research's objective is to expand researches related to language delay, because we only have a few researches on this topic and its impacts on the deaf. This research’s general objective is to analyze how the process of language delay works on deaf students in the school environment and which impacts it has on those students. The specific objectives were to analyze the deaf student’s process of language acquisition at school - Pointing out the loss to the deaf student when facing language delay. - Pointing out the positive impacts that language acquisition generates for the student in the social and school environment. The theoretical support with researches concerning each topic, starting by the human brain (GROLLA e SILVA, 2014 E CUNHA, 2013), language acquisition (GROLLA e SILVA, 2014; GROLLA, 2006; SANTOS, 2004; ARAUJO e BUENO, 2018; LORANDI, CRUZ e SCHERER, 2011; FIORIN, 2013), deaf's language acquisition (QUADROS e CRUZ, 2011; QUADROS e PIZZIO 2011; LORANDI, CRUZ e SCHERER, 2011) language delay (CORDEIRO, 2021; NADER, 2011; NADER e NOVAES-PINTO, 2011; GUARANY, ARAGÃO e COSTA, 2021; PIZZIO e QUADROS, 2011; PERLIN; STROBEL, 2009). The research has been developed in a school for the deaf located in the city of Manaus/AM, that uses Libras as a language of instruction.Data collection was carried out through interviews and questionnaires, with two kinds of questionnaires,one with an investigative approach, and another specifically developed for each researched group.The research participants were two school pedagogues, two hearing teachers, two deaf teachers, and two deaf students. The results showed that the process of language acquisition occurs through the teaching of Libras and contact with deaf teachers and students, the late process generates loss to the deaf both cognitively and socially and there is a significant impact on the student's school and social development when they start the process of acquiring Libras.